2017
DOI: 10.1002/stab.201710476
|View full text |Cite
|
Sign up to set email alerts
|

Einblick in das Vorspannverhalten von geschraubten Verbindungen aus nichtrostendem Stahl

Abstract: Herrn Univ.‐Prof. em. Dr.‐Ing. Herbert Schmidt zur Vollendung seines 80. Lebensjahres gewidmet Vorgespannte geschraubte Verbindungen aus nichtrostendem Stahl sind derzeit normativ nicht zulässig. Dennoch besteht der Wunsch seitens der Bauausführenden, in Spezialfällen diese Art von Verbindungen tragsicherheitsrelevant oder auch nur aus Gebrauchstauglichkeitsgründen auszuführen. Gemeinhin wird den vorgespannten Verbindungen aus nichtrostendem Stahl unterstellt, dass sie sehr hohen Vorspannkraftverlusten infolge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 2 publications
0
4
0
6
Order By: Relevance
“…6. It could be shown that the accuracy of the instrumented bolts with implanted strain gauges for measuring the preload inside the bolts is in principle acceptable, see also [12] and [13], but it has also to be pointed out that viscoplasticity occurs already during the preloading process of the stainless steel which means that these changes in the strain were measured by the strain gauges as well. This yielded to deviating values in comparison to the real 1) all bolts were preloaded to the F p,C level 2) clamping length 3) property class…”
Section: Stress Relaxation Results Fitted To the Hart's Modelmentioning
confidence: 99%
“…6. It could be shown that the accuracy of the instrumented bolts with implanted strain gauges for measuring the preload inside the bolts is in principle acceptable, see also [12] and [13], but it has also to be pointed out that viscoplasticity occurs already during the preloading process of the stainless steel which means that these changes in the strain were measured by the strain gauges as well. This yielded to deviating values in comparison to the real 1) all bolts were preloaded to the F p,C level 2) clamping length 3) property class…”
Section: Stress Relaxation Results Fitted To the Hart's Modelmentioning
confidence: 99%
“…To close these gaps of knowledge, the European research project "Execution and reliability of slip resistant connections for steel structures using CS and SS" (SIROCO), funded by the Research Fund for Coal and Steel (RFCS) of the European Community (RFSR-CT-2014-00024), investigated, besides others, the creep and relaxation behaviour as well as the tightening and the basic preloading behaviour of austenitic and duplex (super duplex, duplex and lean duplex) stainless steel bolting assemblies according to EN ISO 4014/4017. Some results of the investigations have already been published in (5)(6)(7)(8)(9)(10). Within this contribution a short summary of the main findings is given.…”
Section: Introductionmentioning
confidence: 93%
“…An dieser Stelle ist es wichtig, darauf hinzuweisen, dass der Einsatz von vorgespannten Schraub(en)verbindungen aus nichtrostenden Stählen zurzeit normativ nicht geregelt bzw. sogar ausgeschlossen ist . Gemäß ÖNORM EN 1090‐2 dürfen Schrauben aus nichtrostendem Stahl in planmäßig vorgespannten Verbindungen nicht eingesetzt werden, „sofern nichts anderes festgelegt wird“, wobei sie dann als besondere Verbindungsmittel zu behandeln sind.…”
Section: Einführung Und Normative Situationunclassified